NSF-NSDL GREEN Project: A Digital Library Partnership of Academia, Government, and Industry. - Laura M. Bartolo; Vinod K. Tewary; Gregory M. Shreve; Adam C. Powell IV; Marcia L. Zeng (Issues in Science and Technology Librarianship, 2002)
The Green's Function Research and Education Enhancement Network (GREEN) is part of the National Science Foundation's National Science Technology, Engineering, and Mathematics Education Digital Library (NSDL-STEM) Program ({http://nsdl.org/}). The NSF GREEN digital library is a collaboration of materials scientists from the National Institute of Standards and Technology (NIST), the Massachusetts Institute of Technology, and other universities partnered with information scientists at Kent State University. The primary goal of the collaboration is to build a collection of authoritative digital resources integrating education and research in the area of Green's functions.